Ectodermal Defects and Anal Atresia in a Child with a TP63 Mutation‐Expanding the Phenotypic Spectrum. Issue 3 (10th September 2014) - Ruml, Jelena; Cuturilo, Goran; Lukac, Marija; Peters, Hartmut
Abstract Ectodermal dysplasias caused by mutations in the TP63 gene comprise a group of disorders characterized by a spectrum of ectodermal changes, orofacial clefting, and split hand or foot malformation. We report on a boy with a mutation located in the DNA‐binding domain of the TP63 gene with atypical phenotype. These data provide additional evidence of the great variability seen in TP63‐related disorders and further delineation of genotype‐phenotype correlations.